UNMASKING FINANCIAL DECEPTION: UNRAVELING THE FRAUD HEXAGON’S INFLUENCE ON DETECTING FINANCIAL STATEMENT FRAUD IN INDONESIAN PUBLIC COMPANIES - Theresia Wijaya; Armanto Witjaksono (Bina Nusantara University, 2023)
This study examines the influence of the fraud hexagon on the likelihood of financial statement fraud in Indonesian public companies with stock values below IDR 100 that were listed on the Indonesia Stock Exchange (IDX) from 2018 to 2020. The study population comprises sixty companies with stock values below IDR 100 for three consecutive years listed on the IDX. The objective sampling technique was employed to select a sample of 48 companies that met the research criteria, resulting in 144 observations. Data analysis was performed using logistic regression. The findings reveal that financial stability and change in auditors significantly impact identifying financial statement fraud, while financial targets, changes in directors, collusion, inefficient monitoring, and the frequency of C.E.O. photos show no influence. These results provide valuable insights for detecting and preventing financial statement fraud in Indonesian public companies with low stock values.